Jepun” Competitive Strategy Analysis of The Koi Guest House Business for Sustainable Income - Parwati, Ni Made Sri; Gorda, A.A.N. Oka Suryadinatha (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze competitive strategies that support sustainable income for The Koi Guest House. The Koi Guest House utilizes several strategic advantages to support sustainable income in the Canggu, Bali accommodation market. Strategic location in the center of Canggu. The facilities offered are quite attractive with relatively affordable prices. Friendly staff service and attractive guest house design. However, The Koi Guest House faces several weaknesses, including competition with superior facilities that must be addressed to maintain service quality. On the other hand, opportunities such as positive reputation, technological advances, and effective promotions can be utilized to increase visibility. Threats from intense competition and increasingly tight promotional challenges require a strong differentiation strategy. The Koi Guest House adopts a differentiation strategy called JEPUN which integrates Balinese cultural elements and utilizes digital marketing. This study provides guidance for future researchers to explore aspects such as competitor analysis, digital marketing effectiveness, tourist preferences, technological innovation, and sustainability practices. By following this guide, it is hoped that the study can provide in-depth insights and relevant strategies to improve business competitiveness and success in the accommodation market in Bahasa Indonesia.